Preliminary report: Force sensor for rowing biomechanics - Kulkarni, N.; Kaur, S.; Ryan, O.; Topercer, B.; Bhatia, S.; Wadzinski, E. (University of Wisconsin-Madison, 2023)
Elite rowers that engage in a high volume of training can suffer from a variety of injuries, the most common occurring in the lumbar spine [1]. As rowing is a full-body movement, perfecting technique and maintaining proper form is essential to preventing such injuries and improving performance overall [2]. The UW-Madison women`s rowing team is seeking a way to measure real-time biomechanical data in the form of approximate foot force in order to determine the presence of any bodily asymmetries and correct athletes` form. Existing products such as the BioRow Force Plates, often involve expensive and highly advanced equipment such as small, accurate load cell sensors [3]. In order to achieve a more affordable solution that still maintains an appropriate level of accuracy and does not disrupt users` rowing technique, several designs with cheaper alternatives to market-brand force cells were considered. The preliminary design that was deemed most suitable, the Force-Sensitive Resistor, consists of a circuit-based sensor system that is predicted to be seamless and an accurate assessor of force magnitude [4]. Through use of an Arduino microprocessor which will connect a laptop for display, results will be presented to users in a straightforward manner. Upon completion of a working prototype and implementation into the necessary environment, testing will be performed to evaluate the device`s capabilities and performance, after which the design will either be revised or finalize.